(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2025)
This article examines the physicochemical characteristics of the main rivers in the central part of the Chui region, which is important for assessing the state of water resources in the region. The analysis includes the study of the chemical composition of water, pollution levels, as well as physicochemical parameters such as pH, temperature, dissolved oxygen content, mineralization, etc. The results of the study allow us to identify trends in water quality changes depending on anthropogenic load and climatic factors. The physico-chemical analysis of the main rivers in the central region of Chui oblast revealed that the concentration of heavy metals is below the maximum permissible concentration (hereinafter referred to as the MPC). The concentration of cadmium was found to be relatively high in the Ala-Archa river. With regard to cation concentration, the maximum allowable concentration (MAC) of magnesium was exceeded in the Sokuluk-2 river (9.39 mg/l, 03.18). The water samples from the Alamedin River and the Sokuluk River exhibited relatively elevated levels of sodium. The Sokuluk River. The Sokuluk River exhibited relatively elevated calcium concentrations. The concentration of hydrocarbonates, fluorides, chlorides, nitrates and sulphates in the river waters of Chui oblast analysed in this study was below the maximum allowable concentration (MAC). Fluoride levels were found to be elevated in both the Sokuluk River and the Chui River. The Sokuluk River and the Ala-Archa River. In conclusion, the findings of this study provide a foundation for further environmental assessments and the formulation of water management strategies.